IDENTIFICATION OF VARIOUS MARKETING RELATED CHALLENGES OF AGRO BASED PUBLIC SECTOR UNDERTAKINGS IN KERALA - Jiji S. P. AND Clement Sudhahar (INTERNATIONAL JOURNAL FOR INNOVATIVE RESEARCH IN MULTIDISCIPLINARY FIELD, 2018)
The Kerala’s economy is basically agrarian. In spite of economic development and industrialization, agriculture is the spine of the Kerala’s economy. Distant from those who are unswervingly occupied in the agrarian sector, a large number of the population is also betrothed in agro-based activities. Agriculture meets the foods desires of large population of Kerala. It warrants food security for the state. Marketing is the crux of the whole food and agricultural problem in almost all states, especially in the state of Kerala. It would be ineffective to raise the agricultural production as well as output, if not means could be found to move the agricultural produce from the producers' field to the consumers' storeroom at a price which corresponds to flaxen remuneration to the producers on the one side and the consumers’ capability to pay on the other side. It is in this deference, that the Agro Based Public Sector Undertakings in Kerala afford an organized forum for selling the agricultural produce of farmers at a fair price and also proffer dependable and contemporary means to vie with the private enterprises which is better placed in terms of technical and financial resources. Thus, the agricultural marketing and the agri-business of Agro Based Public Sector Undertakings dwell in an imperative place in the overall stratagem for agricultural development in Kerala. Hence, the marketing of Agro Based Public Sector Undertakings are essential for the expansion of agricultural community and the government must catch all the indispensable steps to revitalize them from their dormancy and thereby facilitate the agriculturists to get the maximum promising prices